China’s Conservation Strategy Must Reconcile Its Contemporary Wildlife Use and Trade Practices - Jiao, Yunbo; Lee, Tien Ming (Frontiers in Ecology and Evolution, 2021)
China’s supply-side conservation efforts in the past decades have led to two bewildering juxtapositions: a rapidly expanding farming industry vs. over-exploitation remaining one of the main threats to Chinese vertebrates. The COVID-19 was also the second large-scale zoonotic disease outbreak since the 2002 SARS. Here we reflect on China’s supply-side conservation strategy by examining its policies, laws and practices concerning wildlife protection and utilization, and identify the unintended consequences that likely have undermined this strategy and made it ineffective in protecting threatened wildlife and preventing zoonotic diseases. We call for China to overhaul its conservation strategy to limit and phase out risky and unsustainable utilization, whilst improving legislation and enforcement to establish full chain-of-custody regulation over existing utilization.